Biallelic mutations in Sperm flagellum 2 cause human multiple morphological abnormalities of the sperm flagella (MMAF) phenotype. Issue 5 (23rd July 2019) - Sha, Yanwei; Liu, Wensheng; Wei, Xiaoli; Zhu, Xingshen; Luo, Xiangmin; Liang, Lei; Guo, Tonghang
Abstract: Male patients with multiple morphological abnormalities of the sperm flagella (MMAF) are infertile and exhibit absent, short, coiled, bent and/or irregular sperm flagella. Mutations in the SPEF2 gene reduce sperm motility and cause sperm tail defects in animal models and humans. In the present study, we performed a genetic analysis on an MMAF patient and identified novel biallelic mutations in the SPEF2 gene. The biallelic mutations were confirmed by Sanger sequencing and in silico analysis revealed that, these variations were deleterious. The expression of truncated SPEF2 protein was reduced significantly in the patient's spermatozoa. The spermatozoa harbored biallelic mutations and showed severe ultrastructural defects in the axoneme and mitochondrial sheath. Our data suggest that biallelic mutations in SPEF2 can cause severe sperm flagellum defects, thus providing a novel candidate genetic pathogen for the human MMAF phenotype. Abstract : The spermatozoa of the MMAF patient harbored the biallelic mutations showed severely ultrastructural defects in axoneme and mitochondrial sheath. The biallelic mutations generated truncated protein that contains the full N‐terminal, which confirmed by the constructed mutant plasmids The expression of truncated SPEF2 protein level was reduced significantly in the patient's spermatozoa.